1998
DOI: 10.1128/aac.42.11.3024
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Erythromycin-Resistant Isolates of Staphylococcus aureus Recovered in the United States from 1958 through 1969

Abstract: We tested 16 erythromycin-resistant clinical isolates of S. aureus, recovered from patients hospitalized in the United States from 1958 to 1969, for the presence of ermA,ermB, and ermC by using PCR. Fifteen of 16 isolates contained at least one copy of ermA; the remaining isolate, which was also clindamycin resistant, containedermB. Eight of the 15 isolates harboring ermA, all of which were inducible, contained a single copy of the gene in the chromosome, while the remaining seven isolates had two copies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 29 publications
0
13
1
1
Order By: Relevance
“…aureus RN4220- msrA , and S . aureus 6520- ermB ) controls were included as described by Nicola et al [ 6 ]. A 2ul aliquot of each supernatant containing extracted DNA was used as templates for PCR to amplify ermA , ermB , ermC and msrA genes ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…aureus RN4220- msrA , and S . aureus 6520- ermB ) controls were included as described by Nicola et al [ 6 ]. A 2ul aliquot of each supernatant containing extracted DNA was used as templates for PCR to amplify ermA , ermB , ermC and msrA genes ( Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…While there are many reports on inducible resistance of S. aureus in developed as well as developing countries [ 6 9 ], there is limited data about CL resistance in Uganda and in the region only one study reported on inducible CL resistance in Tanzania by Mshana et al . [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In S. aureus , MLS resistance has two phenotypes. The first is due to ribosomal modification by 23S rRNA methylases, mediated primarily by ermA , ermB or ermC (found on plasmids or chromosomes), preventing antimicrobial agents from binding to their ribosomal target site [5,6]. The second resistance type is mediated by msrA and involves the active efflux of the antimicrobial agent by an ATP‐dependent pump, thereby maintaining intracellular concentrations below the level required for binding to ribosomes [6].…”
Section: Emergence Of Antimicrobial Resistancementioning
confidence: 99%
“…However, to consider all ER‐R staphylococci as CL‐R would lead to the denial of an effective and safe therapy for patients infected with isolates that have only the macrolide efflux mechanism [6]. The frequencies of the different resistance patterns vary widely among clinical staphylococcal isolates according to the patient group and geographical location [1,2,8,9]. Therefore, routine testing also helps to clearly identify those isolates that remain susceptible to clindamycin despite macrolide resistance, the other aim of routine screening [1,2].…”
Section: Incidence Of Inducible and Constitutive Resistance To Erythrmentioning
confidence: 99%